2021
DOI: 10.1093/mnras/stab2766
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the characteristics of magnetars born in death of massive stars and merger of compact objects with swift gamma-ray burst data

Abstract: Assuming that the shallow-decaying phase in the early X-ray lightcurves of gamma-ray bursts (GRBs) is attributed to the dipole radiations (DRs) of a newborn magnetar, we present a comparative analysis for the magnetars born in death of massive stars and merger of compact binaries with long and short GRB (lGRB and sGRB) data observed with the Swift mission. We show that the typical braking index (n) of the magnetars is ∼3 in the sGRB sample, and it is ∼4 for the magnetars in the lGRB sample. Selecting a sub-sam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 91 publications
1
8
0
Order By: Relevance
“…Overall, magnetars as the central engine powering sources can explain the different types of light-curve properties with diverse sets of physical parameters like (10 14 -10 15 gauss) and (a few ms), see Duncan & Thompson (1992). Hence, and values of a newborn magnetar can govern the energy of the resulting GRB and SN, e.g., a fast-rotating magnetar may produce a more energetic GRB (Zou et al, 2019(Zou et al, , 2021. The difference in properties of magnetars originated from the core-collapse of a massive star and the merger of compact objects are presented by Zou et al (2021).…”
Section: Magnetars and Versusmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, magnetars as the central engine powering sources can explain the different types of light-curve properties with diverse sets of physical parameters like (10 14 -10 15 gauss) and (a few ms), see Duncan & Thompson (1992). Hence, and values of a newborn magnetar can govern the energy of the resulting GRB and SN, e.g., a fast-rotating magnetar may produce a more energetic GRB (Zou et al, 2019(Zou et al, , 2021. The difference in properties of magnetars originated from the core-collapse of a massive star and the merger of compact objects are presented by Zou et al (2021).…”
Section: Magnetars and Versusmentioning
confidence: 99%
“…Hence, and values of a newborn magnetar can govern the energy of the resulting GRB and SN, e.g., a fast-rotating magnetar may produce a more energetic GRB (Zou et al, 2019(Zou et al, , 2021. The difference in properties of magnetars originated from the core-collapse of a massive star and the merger of compact objects are presented by Zou et al (2021). They found that the magnetars associated with the core-collapse of massive stars exhibit weaker and a shorter , nearly one to two orders of magnitude compared to those generated from the binary compact mergers.…”
Section: Magnetars and Versusmentioning
confidence: 99%
See 1 more Smart Citation
“…Lasky et al (2017) has constrained the braking indices of the magnetars by using the observed X-ray light curves. Lü et al (2019) and Zou et al (2021) systematically calculated the distribution of the braking indices of magnetars in short and long GRBs, the results show that the braking indices of a number of GRBs are between three and five, implying GW emission already existed in the process of magnetars' spin-down.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to their large energy reservoirs, magnetars have also been invoked as the central engines in a variety of transients, from compact object mergers, which produce short gamma-ray bursts (GRBs, Bucciantini et al 2012;Gompertz et al 2013;Rowlinson et al 2013;Gompertz et al 2014;Metzger & Piro 2014;Zou et al 2021), corecollapse long GRBs (Wheeler et al 2000;Komissarov & Barkov 2007;Metzger et al 2011), superluminous supernovae (Kasen & Bildsten 2010;Woosley 2010;Metzger et al 2015) and fast blue optical transients (Prentice et al 2018;Mohan et al 2020). Many fast radio burst models also implicate magnetars (e.g.…”
Section: Introductionmentioning
confidence: 99%